Development of Delivery Systems Enhances the Potency of Cell-Based HIV-1 Therapeutic Vaccine Candidates. (21st April 2021) - Hadi, Amin; Rastgoo, Abbas; Eskandarian, Maryam; Haghighipour, Nooshin; Bolhassani, Azam
Abstract : An effective therapeutic vaccine to eradicate HIV-1 infection does not exist yet. Among different vaccination strategies, cell-based vaccines could achieve in clinical trials. Cell viability and low nucleic acid expression are the problems related to dendritic cells (DCs) and mesenchymal stem cells (MSCs), which are transfected with plasmid DNA. Thus, novel in vitro strategies are needed to improve DNA transfection into these cells. The recent study assessed immune responses generated by MSCs and DCs, which were derived from mouse bone marrow and modified with Nef antigen using novel methods in mice. For this purpose, an excellent gene transfection approach by mechanical methods was used. Our data revealed that the transfection efficacy of Nef DNA into the immature MSCs and DCs was improved by the combination of chemical and mechanical (causing equiaxial cyclic stretch) approaches. Also, chemical transfection performed two times with 48-hour intervals further increased gene expression in both cells. The groups immunized with Nef DC prime/rNef protein boost and then Nef MSC prime/rNef protein boost were able to stimulate high levels of IFN- γ, IgG2b, IgG2a, and Granzyme B directed toward Th1 responses in mice. Furthermore, the mesenchymal or dendritic cell-based immunizations were more effective compared to protein immunization for enhancement of the Nef-specific T-cell responses in mice. Hence, the use of chemical reagent and mechanical loading simultaneously can be an excellent method in delivering cargoes into DCs and MSCs. Moreover, DC- and MSC-based immunizations can be considered as promising approaches for protection against HIV-1 infections.